Establishing energy benchmarks for commercial buildings in the City of Cape Town - Martin, Caroline (Energy Research Centre, 2015)
The South African Government has ambitious aspirations relating to energy efficiency in their commercial building stock, but no clear strategy for tackling existing buildings. This research redresses this by examining international approaches to the benchmarking process and applies these in the context of South Africa.